The Federal Democratic Republic of Ethiopia : Request for a 14-Month Arrangement under the Exogenous Shocks Facility-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Federal Democratic Republic of Ethiopia. (IMF Staff Country Reports; Country Report, 2009)
Facing declining reserves and high inflation, Ethiopian authorities have implemented an effective macroeconomic adjustment package supported by the IMF under the rapid-access component of the Exogenous Shocks Facility. The global recession is putting renewed pressure on the external position, via weaker export receipts and remittances and slowing inward direct investment. Supporting structural measures focus on tax reform, the control of public enterprise borrowing, and the control of liquidity through indirect instruments.